Relationship between 6‐ and 9‐month progression‐free survival and overall survival in patients with metastatic urothelial cancer treated with first‐line cisplatin‐based chemotherapy. Issue 16 (29th May 2013) - Galsky, Matthew D.; Krege, Susan; Lin, Chia‐Chi; Hahn, Noah; Ecke, Thorsten; Moshier, Erin; Sonpavde, Guru; Godbold, James; Oh, William K.; Bamias, Aristotle
Abstract : BACKGROUND: Use of progression‐free survival (PFS) as a clinical trial endpoint in first‐line treatment of patients with metastatic urothelial carcinoma (UC) is attractive, but would be enhanced by establishing a correlation between PFS and overall survival (OS). METHODS: Data was pooled from 7 phase 2 and 3 trials evaluating cisplatin‐based chemotherapy in metastatic UC. An independent cohort of patients enrolled on a phase 3 trial was used for external validation. Landmark analyses for progression at 6 and 9 months after treatment initiation were performed to minimize lead‐time bias. A proportional hazards model was used to assess the utility of PFS for predicting OS. RESULTS: A total of 364 patients were included in the initial cohort. The median PFS was 8.21 months (95% confidence interval = 7.43, 8.39) and the median OS was 13.50 months (95% confidence interval = 11.80, 15.67). In the landmark analysis, the median OS for patients who progressed at 6 months was 3.87 months compared with 15.06 months for those patients who did not progress ( P  < .0001) and the median OS for patients who progressed at 9 months was 5.65 months compared with 21.39 months for those patients who did not progress ( P  < .0001). A Fleischer model demonstrated a statistically significant dependent correlation between PFS and OS. The findings were externally validated in an independent cohort. CONCLUSIONS: PFS at 6 and 9 months predicted OS in this analysis of patients with metastatic UC treated with first‐line cisplatin‐based chemotherapy and could potentially serve as endpoints in (randomized) phase 2 trials to screen the activity of novel regimens. Cancer 2013;119:3020—3026 . © 2013 American Cancer Society . Abstract : Response rate has traditionally been used as the primary endpoint of phase 2 trials in metastatic urothelial cancer but may be problematic in screening the activity of novel combination regimens. The current analysis demonstrates that progression‐free survival, measured at fixed time points, is highly correlated with overall survival in patients with metastatic urothelial cancer treated with cisplatin‐based chemotherapy and may be a more attractive intermediate endpoint in this clinical disease state.